Algorithm and ninhydrin method allow for measurement of the postprandial appearance of peptides in blood - Stefan G. Pierzynowski; Piotr Wychowański; Wiesław Szczesny; Robert Galloto; Kamil Zaworski; Dominika Szkopek; Jarosław Woliński; Janine Donaldson; Kateryna Pierzynowska (Scientific Reports)
Abstract The recognition of amine groups by ninhydrin, along with a simple mathematical algorithm, showed that di- and tripeptides derived from dietary protein are the major end products of protein digestion entering the blood postprandially. There are thousands of oligopeptides appearing in the gut during protein digestion. However, the presented study on a pig model clearly shows that peptides longer than tri-amino acid peptides do not appear postprandially in the blood in nutritional amounts. We hypothesize that the measurement of postprandial free amino acids, di- and tripeptides and proportions between these components could be a useful, desirable tool both in laboratory and clinical practice, which could be used to determine the metabolic importance of protein digestion end products in health and disease.